Development of MSME potential through branding and digital marketing - Muhammad Eko Atmojo; Gerry Katon Mahendra; Vicky Alfitra Perdana (University of Merdeka Malang, 2023)
The outbreak of the COVID-19 pandemic has had a major impact, particularly on the economic sector, including Micro, Small and Medium Enterprises (MSMEs). These businesses have a very important role in the economy, especially in the Hargorejo Village area. A strong branding strategy with a focus on quality is essential to increase product reach and competitiveness. This community service aims to improve the community's economy and support the community by actively providing assistance to MSMEs in Hargorejo Village, Kokap District, Kulonprogo Regency, Yogyakarta Special Region. The methods used in this community service include outreach, training, and evaluation for MSME participants. The training curriculum covers topics such as the use of technology in MSME products, branding, packaging, and the use of online markets. After completing the training, MSME participants gain a deeper understanding of the importance of using technology in marketing their products. In addition, real improvements can be seen in the branding and packaging of MSME products. This positive transformation can be seen from the post-training assessment which shows that 64% of MSME participants now understand the importance of integrating IT, branding, packaging, and effective online markets into their business strategy. It is hoped that this increased awareness can provide significant benefits for MSME players, especially by strengthening product marketing efforts and improving the overall welfare of MSME stakeholders.